Enhanced thermal stability of green-emission quantum-dot light-emitting diodes via composition-gradient thick-shell quantum dots. (6th July 2016) - Vu, Hoang-Tuan; Chiang, Ray-Kuang; Huang, Chun-Yuan; Chen, Chih-Jung; Yu, Hsin-Chieh; Lien, Jiun-Yi; Su, Yan-Kuin
Abstract: We investigated the thermal properties of quantum-dot light-emitting diodes (QLEDs) using composition-gradient thick-shell CdSe@ZnS/ZnS QDs. Thick-shell QDs with low defective structures effectively prevented electron–hole pairs from nonradiative Auger recombination. More specifically, defects were prevented from thermal-stress-induced expansion at elevated temperatures and high driving currents. Consequently, 97% of EL remained after the device was thermally stressed at temperatures higher than 110 °C, indicating that the nanostructure design of QDs is an important factor for high-performance QLEDs.